FRI0487 UTILITY OF TRABECULAR BONE SCORE(TBS) FOR FRACTURE RISK ASSESSMENT IN GLUCOCORTICOID-INDUCED OSTEOPOROSIS. (June 2019) - Florez, Helena; Hernández-Rodríguez, José; Muxi, Africa; Carrasco, Josep Lluís; Prieto-González, Sergio; Ruiz-Gaspà, Silvia; Cid, Maria C.; Monegal, Ana; Guañabens, Núria; Peris, Pilar
Abstract : Background: Glucocorticoid-induced osteoporosis (GIOP) is the one of the most common forms of secondary osteoporosis (OP). Fractures in GIOP frequently occur with higher than expected bone mineral density (BMD) values. The Trabecular Bone Score (TBS) is a gray-level textural index derived from DXA images that provides information about bone microarchitecture and fracture risk independently of BMD; therefore, TBS measurement could be useful for identifying patients with high fracture risk associated with glucocorticoid (GC) treatment. Objectives: To analyse the clinical utility of TBS for fracture risk assessment in GC treated patients and compare it with BMD assessment, the gold-standard diagnostic test. Methods: 127 patients on chronic GC treatment (≥5mg/day) were included (mean age 62±18 years, 63% women) in this cross-sectional study. The medical history and anthropometric data were collected, as well as measurements of bone metabolism parameters, bone densitometry (DXA) at lumbar spine and femur (considering OP when T-score ≤-2.5), TBS (considering degraded microarchitecture [DMA] with values <1.230) and dorsolumbar X-ray to assess vertebral fractures (VF). BMD and TBS sensitivity, specificity and positive and negative predictive values (PPV, NPV) were evaluated to determine the diagnostic accuracy of the two methods. Results: Most of the patients were receiving GC treatment for vasculitis or polymyalgia rheumatica over a mean period of 47.7±69 months at a mean daily dose of 14.5mg. 17% had VF, 28% any type of fragility fracture (VF + no-VF), 29% OP and 71% DMA. In patients with VF, low TBS (DMA) was more common than densitometric OP (76%, p=0.03 vs . 38%, p=n.s). Similar results were observed when analysing patients with any fragility fracture (69%, p=0.02 vs . 36%, p=n.s). The diagnostic accuracy of TBS was greater than BMD on evaluating VF, with a sensitivity, specificity, PPV and NPV of 0.76, 0.53, 0.25 and 0.92 for TBS and 0.38, 0.72, 0.22, and 0.85 for BMD, respectively. Specificity increased to 0.89 for VF and 0.9 for any fragility fracture on combining both assessments (OP+DMA). Conclusion: TBS has greater discriminative power than BMD measurement and could be useful as a complementary tool for fracture risk assessment in GIOP. Disclosure of Interests: Helena Florez: None declared, José Hernández-Rodríguez : None declared, Africa Muxi: None declared, Josep Lluís Carrasco: None declared, Sergio Prieto-González: None declared, Silvia Ruiz-Gaspà : None declared, Maria C. Cid Grant/research support from: Kiniksa Pharmaceuticals, Consultant for: Roche, GSK, Janssen, Abbvie, Speakers bureau: Boehringer-Inhelheim, Vifor, Ana Monegal Speakers bureau: Eli Lilly, Amgen, Núria Guañabens Consultant for: Advisory Boards from Amgen, Alexion and UCB, Speakers bureau: Fees and lectures from Eli Lilly, Pilar Peris Speakers bureau: Personal Fees and Non-financial support (attendance to congresses) from Amgen and Eli Lilly